Sinonasal cerebrospinal fluid leaks: Report of the last 15 years - Oliveira, Vitor Manuel (2015)
Objectives: Review of the caseload of sinonasal cerebrospinal fluid (CSF) leaks and evaluation of the experience in endoscopic endonasal management of these skull base defects.Methods: We retrospectively collected data on all cases treated as suspected CSF leak, in Hospital Egas Moniz – Centro Hospitalar Lisboa Ocidental, a referral center, over a 15-year period between January 2000 and 2015.Results: 17 patients with CSF leak were treated by endoscopic endonasal approach. Median age was 54 years (range, 3-78 years), 7 (41%) were male and 10 female (59%). The mean follow up was 13 months (range, 2-58 months). The presenting symptoms were rhinorrhea in 13 patients (76%), headache in 6 patients (35%) and photophobia in 1 patient (6%). The investigation revealed 7 (41%) patients with spontaneous CSF leaks; 5 (29%) patients with iatrojenic injury; 3 (18%) patients with traumatic background; and 2 (12%) tumoral relative. The CSF leaks were located in the ethmoidal fovea/ lateral lamella in 5 patients (29%); cribiform plate in 4 patients (24%); posterior ethmoid fovea in 3 patients (18%); sphenoid in 2 patients (12%); foramen cecum in 1 patient (6%); clivus in 1 patient (6%); and in diaphragm of the suprasellar cistern in 1 patient (6%). We used diluted fluorescein in 5 patients (29%) without any reported complication with the intrathecal injection. Lumbar drainage was used in the post-operative period in 11 patients (65%) with mean of 5 days (range, 4-10 days) of drainage. We report 3 patients (18%) in which the CSF leak recurred and a closure success rate of 82% (n=14) after the first attempt of skull base defect reconstruction. From the 3 patients in which a successful watertight closure was not achieved with the fist attempt, one presented with a gunshot wound with massive skull base injury; one recurred after repeated attempt of repair of an iatrogenic injury resulted from clivus osteoradionecrosis secondary to radiosurgery for nasopharyngeal carcinoma recurrence; and one after a first attempt to seal a spontaneous CSF leak.Conclusion: The transnasal endoscopic approach has excellent results in skull base reconstruction. The advantages of transnasal endonasal endoscopic approaches allowed its usage as preferred technique in the treatment of sinonasal CSF leaks. The success of the skull base reconstruction is based in the correct identification of the fistula tract and the preparation of the skull base defect boundaries, as well as, by comprehensive knowhow of the reconstruction techniques and its judicious application in the panning procedure.